Development of a bionematicide from crude extracts of cucumis africanus fruit (Original) (REDEL. Revista Granmense de Desarrollo Local, 2021)
A 14-day experiment was conducted at the University of Limpopo laboratory of nematology to determine the optimum quantity of plant material required for producing a bionematicide from Cucumis africanus fruit with a pH value below 3.5. Seven treatments comprising of 0, 20, 40, 80, 160, 320 and 640 g of ground fruit of Cucumis africanus were arranged in RCBD with 5 replications. The plant material was fermented in 20 L sealed containers containing 300 ml effective micro-organisms (EM), 300 ml molasses and 100 g of brown sugar. At the end of 7, 10 and 14 days of fermentation pH and Electrical Conductivity (EC) were measure. In conclusion electrical conductivity (EC) was proportional to the amount of plant material and pH inversely proportional. Therefore, the optimum quantity of plant material required for producing a bionematicide from fermented crude extracts of Cucumis africanus fruit was determined at 20 to 160 g in a 14-day fermentation time, yielding a pH below 3,7 at an average day/night temperature of 26ºC. In terms of plant material economy, 20 g ground fruit of Cucumis africanus fruit is recommended to produce a bionematicide from fermented crude extracts.Keywords: root-knot nematodes, crude extracts, Cucumis africanus, fermentation, effective microorganisms.
Keywords: root-knot nematodes, crude extracts, Cucumis africanus, fermentation, effective microorganisms